2013
DOI: 10.1021/jp404841m
|View full text |Cite
|
Sign up to set email alerts
|

Surface Electronic Structure and Mechanical Characteristics of Copper–Cobalt Oxide Thin Film Coatings: Soft X-ray Synchrotron Radiation Spectroscopic Analyses and Modeling

Abstract: Novel copper−cobalt oxide thin films with different copper/cobalt molar ratios, namely, [Cu]/[Co] = 0.5, 1, and 2, have been successfully coated on aluminum substrates via a simple and cost-effective sol−gel dip-coating method. Coatings were characterized using high resolution synchrotron radiation X-ray photoelectron spectroscopy (SR-XPS) and near edge X-ray absorption fine structure (NEXAFS) spectroscopy, in combination with nanomechanical testing and field emission scanning electron microscopy (FESEM). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…In addition, the obtained hardness values of the present study are generally consistent with those reported by other researchers [45,46]. [21], the results in this work were slightly higher after annealing. Further, following heat treatment, there is an increasing trend in both elastic modulus and hardness for the coatings, albeit this is not so pronounced for hardness.…”
Section: Accepted M Manuscriptsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the obtained hardness values of the present study are generally consistent with those reported by other researchers [45,46]. [21], the results in this work were slightly higher after annealing. Further, following heat treatment, there is an increasing trend in both elastic modulus and hardness for the coatings, albeit this is not so pronounced for hardness.…”
Section: Accepted M Manuscriptsupporting
confidence: 93%
“…Some variations, although not significant, were observed in the stress distributions (Fig. 10), compared to our previous work [21], due to the change in the mechanical properties of coatings after annealing at the temperature of 650 °C Therefore, two implications can be derived from the above analysis. a) Coating delamination would be suppressed, which typically occurs at the interface between the coating and plastically deformed substrate during unloading.…”
Section: Finite Element Modelling (Fem)mentioning
confidence: 55%
See 1 more Smart Citation
“…The absorptance of 83.4% (prior to the addition of an antireflection layer) was accomplished using 0.25 M copper acetate and 0.25 M cobalt chloride (Cu/Co ratio=1) with dip-speed 120 mm/min (four cycles). Nanoindentation test using the Berkovich indenter showed that the coatings have a high wear resistance [115][116][117].…”
Section: Cumno X Spinels and Cu X Co Y O Z Spinel-likementioning
confidence: 99%
“…In the past few decades, various different techniques such as chemical bath deposition [6], cluster beam deposition [7], electro deposition [8], molecular beam epitaxy [9], thermal evaporation, spray pyrolysis [10], sputter deposition [11], metal organic chemical vapour deposition [12], sol-gel dip-coating technique [13][14][15], photo-enhanced chemical vapour deposition [16]and plasma polymerization method [17] have been extensively used to synthesize the thin film coatings for commercial and industrial applications. However, in the recent times, chemical bath deposition technique has been widely used for the development of thin film coatings because its cost effectiveness, minimum materials wastage, does not need sophisticated machineries and can be applied in large area deposition at low temperatures.…”
Section: Introductionmentioning
confidence: 99%